Effect of Peer Group Interaction on Academic Staff Well-being: Case of Makerere University - Mbabazi, Annet (East African Journal of Interdisciplinary Studies, 2024)
Peer group interactions have been less scrutinized in terms of their contribution to the overall quality of teaching in universities. This mixed-methods study investigated the effect of peer group interaction on the well-being of academic staff at Makerere University. Quantitative data was collected using self-administered questionnaires from 382 academic staff proportionally drawn from three colleges and one school, while qualitative data was obtained from four heads, of departments, and four academic staff using a structured interview guide. Qualitative data was analysed using thematic and content analysis inductively, and later both sets were converged to generate summaries of findings. Quantitatively, results show that peer group interaction stood at (r = .252, n = 286, p < .000) suggesting that there was a statistically significant relationship between well-being and Peer group interaction of academic staff at the 5% of significance two-tailed. R2 = 0.60, which implies that it contributed 60% of the change in academic staff well-being at Makerere University. Peer group interaction (18.929, p = 0.00) indicated that the relationship was significant. This was in agreement with qualitative findings, participants who provided positive feedback, described their interaction with peers as positive. Such positive feedback implied participants' interaction with their peers gave them positive experiences. The conclusion is that peer group interaction is a significant predictor of academic staff well-being. Therefore, the management of the university should strengthen interpersonal relationships through social support platforms and foster a culture of open communication and feedback to contribute to overall academic staff well-being. This can be streamlined by fostering strong interpersonal relationships within the academic community, promoting networking events, creating platforms for social support, and emphasizing the importance of building positive relationships with colleagues.